PENCIPTAAN FOTOGRAFI EKSPRESI BANGUNAN CAGAR BUDAYA DENGAN MODIFIKASI TEKNIK KAMERA LUBANG JARUM (KLJ) - J Andrea, Novan (Institut Bisnis dan Teknologi Indonesia, 2021)
The heritage building in Yogyakarta City is a cultural heritage that needs to be preserved. Apart from having historical value, the reserve building is also an aesthetic object for photography. in this photography project, cultural heritage buildings become objects for the creation of expression photography works with the pinhole camera technique). The method used is to apply the principle of a pinhole camera (KLJ) with dark box with a small hole combined with a DSLR camera as a shooting tool. Meanwhile, the media that becomes the area for the reflection of the object image projection uses recycled paper arranged in such a way that it is able to display certain artistic effects in conveying a paradoxical situation for cultural heritage buildings that are used as objects for the creation of this expression photography. The purpose of this project is to create photographic works of art with an expressionism approach that presents distortions of shape that presents an impression of damage and color mixing as an artistic expression that makes this photographic work unique.